Communication Strategy of Agricultural Extension to Motivating and Fostering Sustainable Food Yard Farmer Women’s Group in Binjai City - Ginting, Andriyani Br; Nurbani, Nurbani; Kurniawati, Dewi (Budapest International Research and Critics University, 2021)
This study aims to analyze the communication strategies carried out by Agricultural Extension Officers (PPL) to motivating and fostering the sustainable food yard Farming Women’s Group (KWT) in Binjai city. The research method used is qualitative methods with interpretive descriptive studies. Determination of research informants by purposive sample. Collecting research data through in-depth interviews, observation and documentation. The results showed that the Communication Strategy of Agricultural Extension Officers (PPL) in motivating the Women Farmers Group (KWT) in Binjai City is carried out by means of coordination, identify ideas and interests, visits, reducing distance, establishing familiarity using light communication, being listeners and giving awards. The communication strategy of Agricultural Extension Officers (PPL) in fostering the Women Farmers Group (KWT) is carried out by introducing the public through identification of community conditions and potential areas, compiling materials / messages based on field needs, determining the method of delivering messages, selecting and using the media by face to face through the group and individual approaches and making scheduled meetings. The communication process runs effectively with one-way communication between the PPL and the women farmer groups and transaction communication with the discussion / sharing groups to exchange knowledge between groups of women farmers. The communication process carried out by the Agricultural Extension Officers (PPL) fosters attention, interest, desire, decision and action. Inhibiting factors in developing sustainable food garden activities, namely technical obstacles in the form of adjustments to the time of guidance and ecological obstacles during the Covid-19 pandemic, there were no group coaching activities.